The Relationship between Self-Compassion and Treatment Fatigue in Chronic Kidney Failure Patients Undergoing Hemodialysis - Bashir, Asri; Huda, Chairul; Nafisah, Luluk; Utami, Desti Kurnia; Ghozali, Imam; Ikhsan, Muhammad; Safrullah (LPPM STIKes Muhammadiyah Ciamis, 2025)
Patients with chronic kidney failure undergoing hemodialysis face physical and emotional stress due to long-term therapy. This condition often causes treatment fatigue, which is physical and psychological fatigue that can reduce motivation and adherence to treatment. One of the psychological factors that can help overcome this fatigue is self-compassion, which is the ability to accept yourself with empathy and be loving to yourself. Patients with good levels of self-compassion generally have higher emotional resilience and more positive adaptability. The purpose of this study is to determine the relationship between self-compassion and treatment fatigue in chronic kidney failure patients undergoing hemodialysis. This study uses a descriptive design of correlation with a cross-sectional approach. A total of 60 patients undergoing hemodialysis for at least six months were selected through purposive sampling. Results of this study Most of the respondents were male (56.7%), aged 41–55 years (48.3%), and had undergone hemodialysis for more than two years (66.6%). Based on the level of self-compassion, the majority of respondents were in the medium category (63.3%), while for treatment fatigue, most were also in the medium category (66.7%). The results of the statistical test showed that there was a significant negative relationship between self-compassion and treatment fatigue (r = –0.471; p = 0.001). This means that the higher the patient's self-compassion, the lower the level of treatment fatigue felt. In conclusion, there was a significant negative relationship between self-compassion and treatment fatigue in patients with chronic kidney failure undergoing hemodialysis.